AI-Enabled Business Intelligence and Digital Marketing Performance: The Roles of Customer Insights and Data-Driven Decision-Making - Khaddam, Amineh A.; Alzghoul, Amro; Irtaimeh, Hani J.; Ali, Ahmad (International Review of Management and Marketing, 2026)
The study is based on the serial-mediated model that investigated the relationship between business intelligence capabilities and digital marketing performance using two mediators: customer insights and data-driven decision-making. The study posits that the dynamic capability's view point, business intelligence capabilities allow companies to capture, integrate, analyze, and translate customer and market data into valuable knowledge for digital marketing activities. An explanatory, cross-sectional, quantitative design was used. The data were gathered from 350 employees and managers of Jordanian companies based on a structured questionnaire that are using business intelligence tools and digital marketing activities. The analysis of data was done with structural equation modelling using SmartPLS software. Results indicated that business intelligence capabilities have positive influence on the customer insights and digital marketing performance. Customer insights also positively influence data driven decision making, and Data-driven decision making positively influences digital marketing performance. In addition, the relationships between business intelligence capabilities and digital marketing performance are serially mediated by customer insights and data-driven decision making. The study raises the importance of BI capabilities in enhancing outcomes in digital marketing.